1977
DOI: 10.1099/00221287-99-1-19
|View full text |Cite
|
Sign up to set email alerts
|

Water Status of Rhizobia in Relation to their Susceptibility to Desiccation and to their Protection by Montmorillonite

Abstract: The greater susceptibility to desiccation of the Rhizobiurn legurninosarum group of rhizobia compared with the slow-growing rhizobia is related to the different amounts of water retained by these groups of bacteria at any relative vapour pressure, rather than differences in rates of water movement into or out of the bacteria. The higher retention of water by the R. legurninosarum group at any relative vapour pressure is related to greater availability of adsorptive surface area, and to higher surface energies … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
23
0

Year Published

1984
1984
2016
2016

Publication Types

Select...
2
2
2

Relationship

0
6

Authors

Journals

citations
Cited by 66 publications
(26 citation statements)
references
References 15 publications
3
23
0
Order By: Relevance
“…Bentonite clay, which includes montmorillonite and other smectite group minerals, protected Rhizobium from predation by protozoa in a liquid culture and in soil amended with the clay . Bacterial growth and activity were higher in the presence of montmorillonite clays compared with kaolinite clays and oxides (Bitton et al, 1976;Bushby and Marshall, 1977;Stotzky and Rem, 1966). This differential effect is related to the greater cation exchange capacity and surface area of 2:1 clay particles (Stotzky, 1966), which presumably confer greater protection against desiccation (Bitton et al, 1976;Bushby and Marshall, 1977) than 1:1 clays and oxides.…”
Section: Protected Versus Unprotected Microbial Biomassmentioning
confidence: 99%
See 2 more Smart Citations
“…Bentonite clay, which includes montmorillonite and other smectite group minerals, protected Rhizobium from predation by protozoa in a liquid culture and in soil amended with the clay . Bacterial growth and activity were higher in the presence of montmorillonite clays compared with kaolinite clays and oxides (Bitton et al, 1976;Bushby and Marshall, 1977;Stotzky and Rem, 1966). This differential effect is related to the greater cation exchange capacity and surface area of 2:1 clay particles (Stotzky, 1966), which presumably confer greater protection against desiccation (Bitton et al, 1976;Bushby and Marshall, 1977) than 1:1 clays and oxides.…”
Section: Protected Versus Unprotected Microbial Biomassmentioning
confidence: 99%
“…Several mechanisms of protection of microbial biomass in soils have been proposed: (i) clays promote microbial growth by maintaining the pH in the optimal range (Stotzky and Rem, 1966), (ii) clays adsorb metabolites inhibitory to microbial growth (Martin et al, 1976), (iii) clay-microbe interactions protect the organisms against desiccation (Bitton et al, 1976;Bushby and Marshall, 1977), and (iv) microbes reside in small pores in which they are protected against predation by higher trophic groups, notably protozoa (Elliott et al, 1980;Rutherford and Juma, 1992). Since all of these mechanisms are directly or indirectly related to the reactive surface properties of clays, the protective capacity of soils for microbial biomass has often been related to clay Fig.…”
Section: Protected Versus Unprotected Microbial Biomassmentioning
confidence: 99%
See 1 more Smart Citation
“…Previous studies have shown that slow-growing rhizobia such as CB1809 are less susceptible to desiccation stress than the fast-growing strains of rhizobia such as TA1 (Bushby and Marshall, 1977b;Deaker et al, 2007). This may explain the lack of significant improvement in survival of CB1809 as this strain of rhizobia has an inherently greater capacity for desiccation tolerance than TA1.…”
Section: General Discussion and Conclusionmentioning
confidence: 99%
“…Previous studies have shown that slowgrowing rhizobia such as bradyrhizobia are less susceptible to desiccation stress than the fastgrowing strains of rhizobia such as R. leguminosarum sp. (Bushby and Marshall, 1977b;Deaker et al, 2007).…”
Section: Discussionmentioning
confidence: 99%